Perancangan Purwarupa Desain Kemasan “Bakpia Srikandi Sri Mulia” Menggunakan Konsep Retorika Visual dan Gaya Grafis Victorian dengan Memanfaatkan Teknologi Laser Cutting dalam Pembentukan Struktur Kemasan - Sudjadi Tjipto Rahardjo; Ipung Kurniawan Yunianto (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2018)
Yogyakarta as a city of tourism, for travelers identical to the typical gift food, namely Bakpia. Bakpia small and micro business are spread and continue to grow in various parts of Yogyakarta. Bakpia product innovation continues to be carried out until a variety of Bakpia flavors appear from the taste of black, green beans, cheese, chocolate, to durian, strawberry, and coffee. The innovation of Bakpia flavor turned out to be inversely proportional to the packaging design of Bakpia. Bakpia packaging in the market today tends to be uniform. The uniformity is immediately seen from the form of packaging (packaging structure), as well as the visual appearance of the packaging (graphic design style) that highlight the Bakpia brand in the form of numbers/numbers. This packaging design research design Bakpia Srikandi Sri Mulia aims to produce a packaging design that is creative in the form of packaging (packaging structure) and has an appeal in visual appearance through visualization of a distinctive graphic design style. The research method uses qualitative ethnographic methods. The main data were obtained from interviews with Bakpia Srikandi Sri Mulia businesses to explore the background of the life journey and the Bakpia business. The conclusions of data from interviews & visual data were analyzed with the visual rhetorical theory which resulted in the concept of Bakpia packaging